Religious Human Resources Management: Perichoresis to manage or to be managed? - Halim Wiryadinata (UIN Sunan Gunung Djati Bandung, 2020)
The meaning of the Greek word, which is Perichoresis as co â€“ indwelling or co â€“ inherence in the sight of the Trinity as the dogma of Christian has a broader perspective of mutual interpenetration of Beings. Thus, it leads the author to argue that Perichoresis is terminus technicus in assessing the management of people (Human Resources Management and People Development) to synergize the jobs for maintaining and achieving the goal of the company. Thus, there are three mainstreams of this article, which are: Firstly, I will look at the history of Perichoresis as a terminus technicus; Secondly, I will explore Human Resources Management and People Development as the parallel of Perichoresis; and Lastly, I will construct a concept of Perichoresis as terminus technicus in Human Resources Management and People Development to achieve the vision of the company.Â